2020
DOI: 10.1111/imcb.12418
|View full text |Cite
|
Sign up to set email alerts
|

IL‐21 treatment recovers follicular helper T cells and neutralizing antibody production in respiratory syncytial virus infection

Abstract: Respiratory syncytial virus (RSV) is the major cause of lower respiratory tract infections in children under 1 year. RSV vaccines are currently unavailable, and children suffering from multiple reinfections by the same viral strain fail to develop protective responses. Although RSV‐specific antibodies can be detected upon infection, these have limited neutralizing capacity. Follicular helper T (Tfh) cells are specialized in providing signals to B cells and help the production and affinity maturation of antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Finally, PD-1 and PD-L1 expression on B cells was described to be upregulated by in vitro stimulation with Helicobacter and to mediate Tr1 differentiation ( 456 ). Moreover, PD-L1 upregulation on B cells, associated with T cell exhaustion, was observed in RSV-infected mice ( 457 ) and HIV-infected patients ( 455 ), suggesting a role for PD-L1 + Bregs as a mechanism to limit tissue damage that can be subverted by pathogens in their benefit.…”
Section: Suppressive Mechanisms Of Bregs By Cell Surface-expressed Moleculesmentioning
confidence: 99%
“…Finally, PD-1 and PD-L1 expression on B cells was described to be upregulated by in vitro stimulation with Helicobacter and to mediate Tr1 differentiation ( 456 ). Moreover, PD-L1 upregulation on B cells, associated with T cell exhaustion, was observed in RSV-infected mice ( 457 ) and HIV-infected patients ( 455 ), suggesting a role for PD-L1 + Bregs as a mechanism to limit tissue damage that can be subverted by pathogens in their benefit.…”
Section: Suppressive Mechanisms Of Bregs By Cell Surface-expressed Moleculesmentioning
confidence: 99%
“…Scrutiny of TLS induction in non-tumor bearing animal models has provided with crucial information for the understanding of the complex, tightly regulated, non-redundant mechanisms that lead to initiation, formation and maintenance of these lymphoid ectopic structures (55). Notably, several recent reports have shed new light in the ontogeny of TLS in mouse models of lung disorders (33,(60)(61)(62)(63)(64)(65)(66). In a model of viral infection with respiratory syncytial virus (RSV), Gassen et al reported a RSVdependent down-modulation of both IL-21 and IL-21R expression by lung Tfh cells, accompanied by an up-regulation of PD-L1 expression on resident B cells and DC, resulting in a defective GC formation and anti-RSV antibody response.…”
Section: Learning From Tls Study In Non-tumor Inflammatory Diseases To Better Understand Tls Role In Cancermentioning
confidence: 99%
“…Therapeutic blockade of PD‐L1 restored IL‐21R expression and increased IL‐21 secretion by Tfh cells. In parallel, treatment of RSV-infected mice with IL‐21 decreased the viral load and inflammation, while inducing the formation of TLS and improving the antibody response against RSV in the lung of infected animals ( 60 ). These results highlight the complex interplay between the IL‐21/IL‐21R and the PD‐1/PD‐L1 axes leading to the regulation of Tfh function and TLS formation in RSV-infected lungs.…”
Section: Learning From Tls Study In Non-tumor Inflammatory Diseases To Better Understand Tls Role In Cancermentioning
confidence: 99%
“…RSV inhibited the humoral immune response of B cells by negatively regulating the expression of IL-21R on the surface of T follicular helper (TFH) cells and IL-21 in immature B cells. These findings may explain the lack of an immune response [72]. In infants with severe respiratory tract infection, the production of IFN-γ by NK cells induced by specific antibodies to RSV was significantly lower than that in uninfected infants, and the activation of these NK cells seemed to be related to Fc fucosylation of RSV-specific antibodies [73].…”
Section: Pathogenesismentioning
confidence: 93%